Multi-dimensional visualization of ingestion, biological effects and interactions of microplastics and a representative POP in edible jellyfish - Jirong Hu; Feiyang Ye; Sufen Zhang; Hao Li; Qian Bao; Jay Gan; Qingfu Ye; Wei Wang (Environment International, 2023)
Due to their ubiquity and potential risks, microplastics (MPs) and nanoplastics (NPs) are concerning environmental issues. Yet there are still significant knowledge gaps in understanding the tissue-specific accumulation and dynamic change of MPs and NPs in the aquatic organism and how these micro/nano-scale emerging contaminants interact with other environmental pollutants such as persistent organic pollutants (POPs). Here, in vivo imaging systems (IVIS), radioisotope tracing, and histological staining were innovatively used to reveal the fate and toxicity of fluorescently-labeled MPs/NPs and 14C-labeled 2,4,4′-trichlorobiphenyl (PCB28) in edible jellyfish Rhopilema esculentum. These contaminants' ingestion, biological effects, and interactions were visualized at cellular, tissue, and whole-body multidimensional levels. Both MPs and NPs were shown to be preferentially accumulated in the mouthlets of oral arms, and most ingested MPs/NPs were present in the extracellular environment instead of being internalized into the mesoglea. Moreover, the presence of MPs or NPs in the seawater significantly inhibited the bioaccumulation of PCB28 in the jellyfish tissue, thus alleviating physiological alteration, gastric damage, and apoptosis caused by PCB28. This study provides a multi-dimensional visualization strategy to display the distribution and biological effects of typical pollutants in marine organisms and offers new insights for understanding the impacts of MPs/NPs and POPs on marine ecosystems.